BIOKONVERSI SELULOSA DARI LIMBAH TONGKOL JAGUNG MENJADI GLUKOSA MENGGUNAKAN JAMUR ASPERGILLUS NIGER - Soeprijanto Soeprijanto (Purifikasi, 2008)
The purpose of this experiment was to obtain glucose from corn-cob through enzymatic hydrolysis using cellulase from Aspergillus niger, and to study the effects of enzyme dose and particle size on the hydrolysis processes. The experiment was started with enzyme preparation from A. niger and cellulase examination. The experiment was then continued with corn-cob composition analysis. Hydrolysis with acid was conducted by immersing the corn-cob in FeTNa solutions. Cellulose hydrolyses using enzyme from A. niger at various particle sizes and enzyme doses were performed and compared. The best activities of cellulase was observed at a concentration 2.257 IU/mL with incubation time of 4 days. Conversion of cellulose to glucose was best (51.01%) at corn-cob particle size of 100 mesh and enzyme volume of 50 mL.